Correction: Removal of safranin-O dye from aqueous solution using modified red mud: kinetics and equilibrium studies. Issue 30 (8th March 2016) - Sahu, Manoj Kumar; Patel, Raj Kishore
Abstract : Correction for 'Removal of safranin-O dye from aqueous solution using modified red mud: kinetics and equilibrium studies' by Manoj Kumar Sahu et al., RSC Adv., 2015, 5, 78491–78501.